2014
DOI: 10.1111/1567-1364.12175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sequential mixed cultures ofWickerhamomyces anomalusandSaccharomyces cerevisiaeon apple cider fermentation

Abstract: The fermentation of cider by mixed cultures of Wickerhamomyces anomalus and Saccharomyces cerevisiae was carried out to study their effect on the cider quality. The results showed that growth of W. anomalus and S. cerevisiae was affected by each other during co-fermentation process. All the mixed cultures produced statistically the same level of ethanol as S. cerevisiae monoculture. The mixed fermentation could produce more variety and higher amounts of acetate esters, ethyl esters, higher alcohols, aldehydes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 40 publications
7
70
0
Order By: Relevance
“…However, in the presence of S. cerevisiae, W. anomalus specifically declined early in fermentation, suggesting an antagonistic interaction between both yeasts [30]. This interaction has also been proposed in apple cider fermentations [31].…”
Section: W Anomalus Is a Ubiquitous Yeast Generally Associated With mentioning
confidence: 53%
See 1 more Smart Citation
“…However, in the presence of S. cerevisiae, W. anomalus specifically declined early in fermentation, suggesting an antagonistic interaction between both yeasts [30]. This interaction has also been proposed in apple cider fermentations [31].…”
Section: W Anomalus Is a Ubiquitous Yeast Generally Associated With mentioning
confidence: 53%
“…Besides the use of Dekkera/Brettanomyces for the production of sour beers, W. anomalus stands out as a promising yeast in brewing fermentations mainly due to its diversified enzymatic activities and bioconversion abilities [92]. The fermentation of cider by sequentially mixed cultures of W. anomalus and S. cerevisiae improved the final quality of cider as a result of a greater variety and amount of esters, higher alcohols, aldehydes, and ketones [31]. P. anomala mixed starters have also been proposed to improve the sensorial quality of the sugar cane spirit cachaça since co-inoculation with S. cerevisiae led to increases in acetate esters and other volatile compounds associated to good sensory descriptors [93].…”
Section: Applications Of W Anomalus Beyond Wine Fermentationmentioning
confidence: 99%
“…In a previous study, we investigated the mechanism of inhibition between S. cerevisiae and W. anomalus isolated from Chinese liquor. The inhibition was not alleviated when glucose and new fermentation medium were added to the fermentation broth, which indicated that the inhibition was not due to the competition for nutrients (25). We also found that the inhibition still existed when we separated them by a dialysis bag for coculture or when the culture supernatant of S. cerevisiae was added to the W. anomalus fermentation medium.…”
Section: Discussionmentioning
confidence: 83%
“…Compounds were identified by comparison with the reference spectra of the National Institute for Standards and Technology (Gaithersburg, MD, USA), the Wiley MS library and the relative peak area (28). Aliquots of wine samples (8 mL) were placed in each SPME vial (15 mL).…”
Section: Volatile Organic Compound Analysismentioning
confidence: 99%